Portal Vein Embolization: Correlation of Future Liver Remnant Hypertrophy to Type of Embolic Agent Used. Issue 3 (August 2018) - Dhaliwal, Surinder K.; Annamalai, Ganesan; Gafoor, Nelofer; Pugash, Robyn; Dey, Chris; David, Elizabeth Nishani
Purpose: The purpose of this study was to compare the effectiveness of portal vein embolization (PVE) with different embolic agents used at our centre. Specifically, the effectiveness of N-butyl cyanoacrylate (NBCA) glue is compared with that of polyvinyl alcohol (PVA) particles. Methods: We performed a retrospective chart review of all patients (N = 77) who underwent PVE at our institution over a 5-year period. Pre- and postprocedural computed tomography or magnetic resonance imaging, when available, were used to measure the volume of total liver volume and future liver remnant (FLR). The absolute values obtained were used to calculate percentage of FLR. The growth in FLR was determined 4–6 weeks after PVE. Technical details of the procedure including the type and amount of embolic agent used were obtained from the chart reviews, electronic patient records, and radiology reports. Statistical analysis was performed using Kruskal-Wallis test, Wilcoxon rank sum test, and the Spearman correlation coefficient with post hoc analysis. Results are expressed as mean ± SD ( P < .05 considered statistically significant). Results: NBCA (n = 29) produced a mean change in FLR of 14.8% compared with 9.3% for PVA particles (n = 24; P = .007). Mean change in FLR was 10.1% in the group where a combination of NBCA and PVA particles was used (n = 24). The effect of glue volume and glue-to-lipiodol ratio on the outcome was not found to be statistically significant ( P = .5 and .7, respectively). Conclusions: We conclude that NBCA glue is a better embolic agent than PVA particles in inducing liver hypertrophy.